Non-invasive brain stimulation in Stroke patients (NIBS): A prospective randomized open blinded end-point (PROBE) feasibility trial using transcranial direct current stimulation (tDCS) in post-stroke hemispatial neglect. Issue 8 (14th September 2021) - Learmonth, Gemma; Benwell, Christopher S.Y.; Märker, Gesine; Dascalu, Diana; Checketts, Matthew; Santosh, Celestine; Barber, Mark; Walters, Matthew; Muir, Keith W.; Harvey, Monika
ABSTRACT: Up to 80% of people who experience a right-hemisphere stroke suffer from hemispatial neglect. This syndrome is debilitating and impedes rehabilitation. We carried out a clinical feasibility trial of transcranial direct current stimulation (tDCS) and a behavioural rehabilitation programme, alone or in combination, in patients with neglect. Patients >4 weeks post right hemisphere stroke were randomized to 10 sessions of tDCS, 10 sessions of a behavioural intervention, combined intervention, or a control task. Primary outcomes were recruitment and retention rates, with secondary outcomes effect sizes on measures of neglect and quality of life, assessed directly after the interventions, and at 6 months follow up. Of 288 confirmed stroke cases referred (representing 7% of confirmed strokes), we randomized 8% (0.6% of stroke cases overall). The largest number of exclusions (91/288 (34%)) were due to medical comorbidities that prevented patients from undergoing 10 intervention sessions. We recruited 24 patients over 29 months, with 87% completing immediate post-intervention and 67% 6 month evaluations. We established poor feasibility of a clinical trial requiring repeated hospital-based tDCS within a UK hospital healthcare setting, either with or without behavioural training, over a sustained time period. Future trials should consider intensity, duration and location of tDCS neglect interventions. Trial registration: ClinicalTrials.gov identifier: NCT02401724 .